'Natural' and 'Unnatural' medical deaths and coronial law: A UK and international review of the medical literature on natural and unnatural death and how it applies to medical death certification and reporting deaths to coroners: Natural/Unnatural death: A Scientific Review. (July 2017) - Harris, Andrew
In the United Kingdom, when people die, either a doctor writes an acceptable natural cause of death medical certificate, or a coroner (fiscal in Scotland) investigates the case, usually with an autopsy. An inquest may or may not follow. The concept of 'natural or unnatural cause' death is not internationally standardized. This article reviews scientific evidence as to what is a natural death or unnatural death and how that relates to the international classification of deaths. Whilst there is some consensus on the definition, its application in considering whether to report to the coroner is more difficult. Depictions of deaths in terminal care, medical emergencies and post-operative care highlight these difficulties. It secondly reviews to what extent natural and unnatural are criteria for notification of deaths in England and Wales and internationally. It concludes with consideration of how medical concepts of unnatural death relate in England and Wales to coroners' legal concepts of what is unnatural. Deaths that appear natural to clinicians and pathologists may be legally unnatural and vice versa. It is argued that the natural/unnatural dichotomy is not a good criterion for reporting deaths under medical care to coroners, but the notification of a medical cause of death, using the International Classification of Disease Codes and the medical professional view as to whether it is scientifically natural, is of great value to the coroner in deciding whether it is legally unnatural.